The Influence of Problem-Based Learning with the Assistance of Geogebra on Student Mathematical Problem-Solving Ability - Samosir, Nurjannah; Salayan, Madyunus (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to analyze the significant effect of the Geogebra-assisted Problem Based Learning model on students’ mathematical problem solving abilities and independent learning. This study uses a quantitative approach to the type of quasi-experimental research, the research design uses a Post-test Only Control Group Design. This study uses only one class. Test the hypothesis in this study using a one-way MANOVA. The sample in this study was class XI-IPA.4 SMA Negeri 1 Galang for the academic year 2022/2023 with a total of 34 students as an experimental class using Geogebra-assisted Problem Based Learning. The hypothesis testing data analysis technique uses the Manova test with the help of SPSS. The results of this study indicate, the results of the MANOVA test with Hotelling’s Trace analysis show a significant value of 0.000 less than 0.05 (H0 is rejected) so it can be concluded that there is a significant influence of the Problem Based Learning model with the help of Geogebra on problem solving abilities and student learning independence .